Hubungan Pengetahuan Remaja dan Pendidikan Ibu terhadap Kejadian Anemia Pada Remaja Putri Di SMPN 02 Rambah Hilir Kabupaten Rokan Hulu - Handayani, Eka Yuli; Sepduwiana, Heny (Jurnal Martenity and Neonatal, 2019)
Anemia is a nutritional problem in the world, especially in developing countries. Young women have a risk ten times more likely to suffer from anemia than young men. Indonesia's health profile records that the Indonesian population classified as adolescents (10-19 years) is around 21% (44 million people) consisting of 50.8% of adolescents and 49.2% of adolescent girls. According to WHO, the incidence of anemia in young women in developing countries is around 53.7% of all young women. According to the IDHS, the prevalence of anemia is 75.9 in young women. Meanwhile the factors of adolescent knowledge, nutritional status, duration of menstruation and mother's education are some of the factors that influence the occurrence of anemia. Anemia in adolescents can have an impact on decreasing work productivity or academic ability in school, because there is no passion for learning and concentration. Anemia can also interfere with growth where height and weight become imperfect. In addition, the immune system decreases easily susceptible to disease. The purpose of this study was to determine the relationship between adolescent knowledge and maternal education on the incidence of anemia in adolescent girls in SMPN 02 Rambah Hilir in 2018. The type of research used was a correlative analytical method with a cross sectional research design carried out at SMPN 02 Rambah Hilir a sample of 62 people by giving 20 questions through a questionnaire. The analysis of the research was carried out by the Chi Square statistical test. The results of this study have a relationship between knowledge of adolescents (P value = 0.001 <0.05) and maternal education (P value = 0.001 <0.05) on the incidence of anemia in adolescent girls. there is a relationship between adolescent knowledge and maternal education on the incidence of anemia in young women. The suggestion in this study is that schools should provide reading books about anemia for students.